A Phase Transition in Theories of Speech: A Metalogue. Issue 3 (2nd July 2016) - Tuller, Betty; Rączaszek-Leonardi, Joanna
ABSTRACT: This article is a metalogue tracing one of Carol Fowler's theoretical contributions to understanding speech perception and, more broadly, cognition. Metalogues, a term coined by Bateson (1972 ), are conversations in which the content is illustrated by the structure. Similarly in this piece, the structure of the exposition embodies the dynamic progression of ideas. In particular, the structure of the text mirrors the perturbations that Fowler's and others' arguments brought to the 1980s view of speech segments. We start with an early, generally accepted theoretical approach (not endorsed by the authors and admittedly oversimplified), of speech segments as abstract and timeless. The text then moves toward and through a phase transition in which ideas, prose, and font become increasingly noisy and unstable until a very different theoretical outlook, espoused by Carol Fowler and colleagues, is established.